Performance and behavior of piglets fed diets with different metabolizable energy levels Desempenho e comportamento de leitões alimentados com dietas com diferentes níveis de energia metabolizável - de Medeiros J.M.* (2023)
© 2023 Universidade Estadual de Londrina. All rights reserved.This study evaluated the effect of different metabolizable energy (ME) levels in diets on digestibility, performance, and feeding behavior of weaned piglets. A digestibility study to determine ME levels was performed using 12 male piglets with 11.5 ± 0.5 kg body weight (BW), in a cross-over design fed with different ME levels (treatments). In the performance study were used 64 female piglets with 7.5 ± 0.8 kg BW, in a randomized block design with four treatments (3.30, 3.40, 3.50, and 3.60 Mcal.kg-1 ME levels), and feeding program with three phases (pre-initial I, pre-initial II, and initial). For feeding behavior, four pens of each treatment were monitored with cameras. The crude-protein digestibility coefficient reduced as dietary ME level increased (P <0.05). In pre-initial I animal performance was not influenced (P <0.05) by ME diet levels, and in the pre-initial II and initial phases, increases in ME caused quadratic (r2 0.99) and linear (r2 0.99) effects on daily feed intake, respectively. When ME levels increased, feed conversion ratio decreased linearly in the pre-initial II phase (r2 =0.98), and quadratically in the initial phase (r2= 0.99). The number and duration of feeder visits linearly decreased as the diet energy levels increased (P <0.05). Weaned piglets can regulate feed intake according to dietary ME levels. The performance of weaned piglets can be maintained using diets containing metabolizable energy levels between 3.30 at 3.60 Mcal.ME.kg-1 if the ratio of nutrients to energy is maintained constant.The feed intake behavior of weaned piglets is influenced by increases in dietary metabolizable energy levels evaluated, resulting in fewer and shorter visits to the feeder.